Pengaruh Work Conflict, Beban Kerja, Personality Type, Stress Kerja Dan Reward Terhadap Kinerja Karyawan Pada Masa Pandemi Covid-19 (Studi pada Karyawan CV. Bola Surya Shuttlecock) - Mega Putri Elissa; Rois Arifin; Afi Rahmat Slamet (UNIVERSITAS ISLAM MALANG, 2022)
The purpose of this study is to find out how employee performance at CV is affected by work conflict, workload, personality type, work stress, and rewards. Bola Surya Shuttlecock and to determine the effect of Work Conflict, Workload, Personality Type, Work Stress, and Reward on the Performance of Staff simultane-ously or in part.This research employs quantitative techniques.Ex-planatory research is the term for this kind of study.This study's population consists of employees of CV. Bola Surya Shuttlecock using snowball sampling numerous as 95 respondents.methods for gathering data using questionnaires and documents. Positive and significant world conflict has no effect on the performance of CV employees Shuttlecock Solar Ball. (2) Workload has a positive and significant impact on the performance of employees at CV. Shuttlecock Solar Ball. (3) Personality type has a positive and significant impact on employee performance at CV. Shuttlecock Solar Ball. (4) Workplace stress has a positive and significant impact on employee performance in CV. Shut-tlecock Solar Ball. (5) Employee performance is not significantly impacted by compensation at CV. Shuttlecock Solar Ball Keywords: Work Conflict, Workload, Personality Type, Job Stress, Reward, Em-ployee Performance